Methods for Matthew - Powell, Mark Allan 1953- (Cambridge Cambridge University Press, 2009)
Today's biblical scholars study the Gospel of Matthew with a wide variety of methods that yield diverse and exciting insights. Methods for Matthew offers a primer on six exegetical approaches that have proved to be especially useful and popular. In each case, a prominent scholar describes the principles and procedures of a particular approach and then demonstrates how that approach works in practice, applying it to a well-known text from Matthew's Gospel. As an added bonus, each of the chosen texts is treated to three different interpretations so that the reader can easily compare the results obtained through one approach to those obtained through other approaches. The reader will learn a great deal about two stories from Matthew ('the healing of a centurion's servant' and 'the resurrection of Jesus') and the reader will also learn enough about each of these six approaches to understand their function in biblical studies today.
The historical-critical method and the Gospel of Matthew / Donald A. Hagner and Stephen E. Young -- Literary approaches and the Gospel of Matthew / Mark Allan Powell -- Feminist criticism and the Gospel of Matthew / Elaine M. Wainwright -- Historical Jesus studies and the Gospel of Matthew / Craig A. Evans -- Social-scientific approaches and the Gospel of Matthew / Bruce J. Malina -- Postcolonial criticism and the Gospel of Matthew / Fernando F. Segovia
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Bible; Bible -- Hermeneutics; Bible -- Criticism, interpretation, etc; Bible -- N.T. -- Matthew -- Hermeneutics; Bible -- N.T. -- Matthew -- Criticism, interpretation, etc; Bible ; Matthew ; Hermeneutics; Bible ; Matthew ; Criticism, interpretation, etc; Aufsatzsammlung